International Mobility of Work and Its Tax Challenges - Pignatari, Leonardo Thomaz (Revista de Direito Tributário Internacional Atual, 2025)
International mobility of work is not something new, but it certainly received new contours after the COVID-19 pandemic. New forms of work emerged or gained a significant boost, such as remote work and digital nomadism. Alongside them, challenges appeared for many areas, including Tax Law. In this sense, the present study aims to examine these challenges from the perspectives of corporate and individual taxation. Historically, physical presence has been an important nexus for determining the tax residence of legal entities and individuals, as well as for allocating taxing powers among Contracting States in double tax treaties. This article questions such a historical nexus, dives into the tax impacts of international mobility of work and presents some alternatives that might be useful to navigate a highly mobile world.